2018
DOI: 10.1002/chem.201705189
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Acid‐Catalyzed Tandem Cyclizations of Tryptamine‐Ynamides Yielding 1H‐Pyrrolo[2,3‐d]carbazole Derivatives

Abstract: Ynamides, as versatile synthetic precursors, have attracted much attention from synthetic chemists and sparked the development of a number of methodologies for the construction of various structures. 1H-Pyrrolo[2,3-d]carbazole is a core scaffold of a series of monoterpene indole alkaloids found in Kopsia, Strychnos, and Aspidosperma, for example. In this study, 1H-pyrrolo[2,3-d]carbazole derivatives were synthesized by a Brønsted acid-catalyzed tandem cyclization starting from tryptamine-based ynamides. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…The subsequent addition of silyl enol ether to the resulting iminium moiety leads to the formation of intermediate C, followed by deauration and cleavage of the silyl group to produce pyrrolo[2,3d]carbazole D. During the course of this study, a related goldcatalyzed cascade cyclization was reported by Yang and coworkers, 12 where the iminium intermediate was trapped by intramolecular nucleophilic attack of hydroxy group (Scheme 1b). Quite recently, the Cheng and Liu group 14 reported an acid-catalyzed cascade reaction of ynamide for the racemic synthesis of pyrrolo[2,3-d]carbazole D using methyl ketone derivative G (Scheme 1c). Herein, we describe a goldcatalyzed cascade reaction of ynamide with silyl enol ether, leading to pyrrolo[2,3-d]carbazole D. A catalytic enantioselective version of the reaction and its application to formal synthesis of vindorosine are also presented.…”
Section: Introductionmentioning
confidence: 99%
“…The subsequent addition of silyl enol ether to the resulting iminium moiety leads to the formation of intermediate C, followed by deauration and cleavage of the silyl group to produce pyrrolo[2,3d]carbazole D. During the course of this study, a related goldcatalyzed cascade cyclization was reported by Yang and coworkers, 12 where the iminium intermediate was trapped by intramolecular nucleophilic attack of hydroxy group (Scheme 1b). Quite recently, the Cheng and Liu group 14 reported an acid-catalyzed cascade reaction of ynamide for the racemic synthesis of pyrrolo[2,3-d]carbazole D using methyl ketone derivative G (Scheme 1c). Herein, we describe a goldcatalyzed cascade reaction of ynamide with silyl enol ether, leading to pyrrolo[2,3-d]carbazole D. A catalytic enantioselective version of the reaction and its application to formal synthesis of vindorosine are also presented.…”
Section: Introductionmentioning
confidence: 99%
“…The latest effort to construct the tetracyclic indoline scaffold by using nucleophilic addition strategy was made by our group. We developed a Brønsted acid catalyzed tandem cyclization of tryptamine‐derived ynamides towards the tetracyclic frameworks (Scheme ) . In this approach, ynamides were utilized as significant building blocks by taking advantage of the substantial advancements in ynamide chemistry in the past decade .…”
Section: Nucleophilic Additionsmentioning
confidence: 99%
“… A Brønsted acid‐catalyzed tandem cyclization of tryptamine‐derived ynamides strategy to tetracyclic indolines 67 (Liu and Cheng et al …”
Section: Nucleophilic Additionsmentioning
confidence: 99%
See 2 more Smart Citations